2015
DOI: 10.1016/j.pmrj.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Exoskeleton‐Based Interactive Video Game System for Upper Extremity Burn Contractures

Abstract: This study demonstrates the feasibility of use of an exoskeleton-based interactive gaming system in the burn population. Future studies are needed that examine the efficacy of tailoring interactive video games to the specific joint impairments of burn survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Importantly, significant changes in multiple outcome measures were observed in the VR group after intervention. Jeffery et al reported that the VR system can be modified to maximize therapeutic benefits such as improving the ROM of the shoulder and elbow joints after burn injury [26]. The tasks in the VR system include ADLs, such as cooking, cleaning windows, squeezing oranges, and turning over pages.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, significant changes in multiple outcome measures were observed in the VR group after intervention. Jeffery et al reported that the VR system can be modified to maximize therapeutic benefits such as improving the ROM of the shoulder and elbow joints after burn injury [26]. The tasks in the VR system include ADLs, such as cooking, cleaning windows, squeezing oranges, and turning over pages.…”
Section: Discussionmentioning
confidence: 99%
“…Additional categories with lower frequency in the retrieved literature were cerebral palsy, hemiparesis, and neurological motor deficits. Furthermore, one study was related to Parkinson disease [19], one study was related to burn contractures [20], two studies addressed patients with brain impairment [21,22], three focused on general cognitive deficits [23][24][25], and other conditions were identified as shoulder [26] or wrist [12,27] injuries.…”
Section: Medical Conditionmentioning
confidence: 99%
“…Besides interest in developing robotic devices identified in the hardware development category, some research teams have also focused on robotic devices that are already available on the market. Several studies used haptic devices such as Phantom Omni [22,[120][121][122], Novint Falcon [77,122,123], Haptic Master [59,[124][125][126][127], and Geomagic Touch [128], whereas others used robotic gloves such as CyberGrasp [124,126,129] and 5DT Data Glove [130,131] or robotic arms such as Barrett Wam [132] and Armeo Spring [20,108,133].…”
Section: Commercial Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROM and data regarding the angles of the hand during its motion constitute another significant group of features that have been commonly used by researchers and health professionals to Several studies [12,20,69,81,98,103,152] referred to the calculation of these kinds of features. Four studies [20,69,98,152] reported that they monitored ROM data (minimum, maximum, and average) for each single joint or exercise movement, and only one study [12] calculated ROM as a summative score of multiple movements or the difference. This extracted feature comprises a valuable tool, as it can be compared across sessions, subjects, or between the impaired and nonimpaired limb of each subject.…”
Section: Extracted Game Featuresmentioning
confidence: 99%